Ecological Studies on Rosa webbiana Wall. Ex Royle in Cold Desert Areas of Spiti Valley in Himachal Pradesh - Singh, R. P.; Negi, D. V.; Chand, Prakash (Indian Forester, 1997)
The present study was conducted in the cold desert areas ofSpiti Valley in the State of Himachal Pradesh. Rosa webbiana, seeds should be treated with concentrated sulphuric acid for 20 minutes duration to enhance its germination. It can be propagated by stem cutting and root suckers. Stem and branches contribute maximum to the total biomass followed by root and leaves in that order. Approximately twenty shoots sprout from single root stock and form a colony over barren slopes which checks the erosion. Total biomass on dry weight basis was 5.42 kg/plant and energy ranged from 3.1 to 4.2 K.cal/g dry weight. An average bush accumulates 20615 K.cal of energy per plant.